If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-67+x-17+3x=30
We move all terms to the left:
2x-67+x-17+3x-(30)=0
We add all the numbers together, and all the variables
6x-114=0
We move all terms containing x to the left, all other terms to the right
6x=114
x=114/6
x=19
| 38-10t=10+4t | | 3(x=2)=4(2x=1)=6x=20 | | 7x-11=10x+5 | | 3x-5=x/1 | | 4=-2r/20 | | q/4+2=9 | | 3y+4y^2=0 | | f/9-9=8 | | 3-(x+7)=3(2x)+1 | | x/(-2)=-6 | | x+10+59=90 | | 2/3=t+6/7 | | 2x*1+89=10x*2 | | (2/3)*y+5=9 | | 7x-5+60=20 | | 20+m=8 | | 9x+15+36=15x-9 | | 42=-7a+7 | | x^2-180x-225=0 | | 5h+25=6h+18 | | 18x=204 | | -2.4x=14.4 | | 16925*x=2898.25 | | .10x+0.05(8-x)=0.10(9) | | 29=y÷4+11 | | x^2+2x2-9x+18=0 | | 11x-6=2x-69 | | x2+2x2-9x+18=0 | | 2x-10=5x+40 | | x3+2x2-9x+18=0 | | 45=36x+24 | | 60=27x+2 |